2012
DOI: 10.1080/01431161.2012.730156
|View full text |Cite
|
Sign up to set email alerts
|

Compact polarimetry assessment for rice and wetland mapping

Abstract: Polarimetric RADARSAT-2 data of rice and wetlands are used to simulate compact polarimetry (CP) mode data from the upcoming RADARSAT Constellation Mission (RCM). The simulated CP data are then used to evaluate the information content for rice and wetland mapping using supervised classification, and the results are compared for linear and circular polarization combinations and polarimetric decompositions from the fully polarimetric data and the simulated CP data. The results are consistent for both rice and wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 34 publications
2
45
0
Order By: Relevance
“…This is mostly as a result of increased confusion with Tundra, for which user's and producer's accuracies were also generally lower for models constructed with simulated RCM data. These results are consistent with [73] who similarly noted a decrease in the classification accuracy of wetlands when substituting quad pol RADARSAT-2 for simulated RCM data. Nevertheless, the authors found that the CP mode still achieved relatively high accuracies, and so suggested it was suitable for broad scale mapping.…”
Section: Comparing Performance Of Random Forest Models Based On Quad supporting
confidence: 81%
“…This is mostly as a result of increased confusion with Tundra, for which user's and producer's accuracies were also generally lower for models constructed with simulated RCM data. These results are consistent with [73] who similarly noted a decrease in the classification accuracy of wetlands when substituting quad pol RADARSAT-2 for simulated RCM data. Nevertheless, the authors found that the CP mode still achieved relatively high accuracies, and so suggested it was suitable for broad scale mapping.…”
Section: Comparing Performance Of Random Forest Models Based On Quad supporting
confidence: 81%
“…This is not a new discovery, and is a consequence of the special interaction of microwaves with inundated rice fields [30,57]. By making use of this interaction, rice fields can be separated from the other land use classes with high accuracy [27,31,58]. Another known fact that can be justified by this study is that only multi-temporal radar acquisitions are adequate to dissolve different crops [20,21].…”
Section: Discussionmentioning
confidence: 82%
“…This allows the user to decompose the SAR backscatter being returned from the objects being sensed into four common scattering types: (1) specular scattering (no return to the SAR), which occurs from smoother surfaces such as calm water or bare soil; (2) rough scattering, which results when there is a single bounce return to the SAR from surfaces such as small shrubs or rough water; (3) volume scattering, which is when the signal is backscattered in multiple directions from features such as vegetation canopies; and (4) double-bounce or dihedral scattering, which results when two smooth surfaces create a right angle that deflects the incoming radar signal off both surfaces such that most of the energy is returned to the sensor. This latter scattering case typically occurs when vertical emergent vegetation is surrounded by a visible, smooth water surface [32,[47][48][49][50][51]. Flooded vegetation can also have a combination of double-bounce and volume backscattering [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…This latter scattering case typically occurs when vertical emergent vegetation is surrounded by a visible, smooth water surface [32,[47][48][49][50][51]. Flooded vegetation can also have a combination of double-bounce and volume backscattering [50,51]. When fully polarimetric SAR images are acquired throughout the growing season, the user can analyze the backscatter response from each stage of the hydrologic and vegetation development (leaf-on and leaf-off) to better understand responses during wetter and dryer periods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation